Colombia’s 2017 Model Bit: Breaking the mould? (2021)
ABSTRACT: This article aims to highlight Colombia’s contribution to the debate on reforming the International Investment Regime (IIR), with its 2017 Model Bilateral Investment Treaty (BIT). It will give some background on Colombia’s investment policy and its 2017 Model. It will then explore Colombia’s Model through: clarification of the language of BIT provisions, increased State Party rights in Investor State Dispute Settlement Procedures, the State’s right to regulate, and investor responsibilities. With Host State regulatory prerogatives and human rights at the core, Colombia puts forward an alternative regional proposal to the IIR reform.